2023
DOI: 10.34312/jjom.v5i1.15556
|View full text |Cite
|
Sign up to set email alerts
|

Pola Faktor Keragaman pada Respons Dikrit

Abstract: In social research, respondents are usually given several questions or indicators for assessment. Responses between respondents may differ even if the same questions or indicators are given. This is one of the causes of the diversity of responses. The diversity of responses is one of the factors that cause response bias in conducting social research. The diversity of responses can come from differences in the thought processes of each respondent. There are three main aspects in the thought process, namely cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Giving allowance/ pocket money to adolescent girls can be a trigger in buying fast food because the greater the allowance earned, the more likely it is to buy or consume fast food because the price of fast food tends to be high. Fast food is often chosen by teenagers because it is simpler than bringing food from home or cooking it yourself (24) The results showed that 45 people (35.4%) of adolescent girls who had eating disorders would have unhealthy eating behavior, which was higher than that of 30 (27%). The results of statistical tests showed that eating disorders affected the unhealthy eating behavior of adolescent girls (p=0.008).…”
Section: Methodsmentioning
confidence: 99%
“…Giving allowance/ pocket money to adolescent girls can be a trigger in buying fast food because the greater the allowance earned, the more likely it is to buy or consume fast food because the price of fast food tends to be high. Fast food is often chosen by teenagers because it is simpler than bringing food from home or cooking it yourself (24) The results showed that 45 people (35.4%) of adolescent girls who had eating disorders would have unhealthy eating behavior, which was higher than that of 30 (27%). The results of statistical tests showed that eating disorders affected the unhealthy eating behavior of adolescent girls (p=0.008).…”
Section: Methodsmentioning
confidence: 99%
“…Another study focused on adult mathematical literacy and found that high school students with strong mathematical abilities could formulate mathematical situations, apply mathematical reasoning, and interpret mathematical solutions, albeit with errors in reasoning and solution interpretation (Lestari et al, 2022). Furthermore, research in Sleman Regency, Indonesia, revealed that high school students generally have low mathematical literacy skills, particularly in formula and application processes, interpretation processes, and various mathematical content areas (Nurjanah & Saputra, 2023). Moreover, a systematic literature review analyzed students' mathematical literacy based on learning styles and cognitive styles, predominantly conducted in high schools in Java, Indonesia (Rum & Juandi, 2022).…”
Section: Introductionmentioning
confidence: 99%